GREEN SYNTHESIS OF COPPER OXIDE NANOPARTICLES USING OCIMUM BASILICUM EXTRACT AND THEIR ANTIBACTERIAL ACTIVITY - Altikatoglu, Melda; Attar, Azade; Erci, Fatih; Cristache, Corina Marilena; Isildak, Ibrahim (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
The investigation aims the synthesis of copper oxide nanoparticles (CuO NPs) using Ocimum basilicum plant extract at room temperature. This method is completely a green method, free from toxic and harmful solvent. The CuO NPs were sytnhesized by mixing copper sulphate dehydrate (CuSO4.5H20) and aqueous Ocimum basilicum leaf extract. The biosynthesized copper oxide nano-particles were characterized by UV-vis spectro-scopy, Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The existence of the CuO NPs was revealed by UV-vis spectroscopy. The FTIR spectra of control (leaf extract) and synthesized CuO NPs identified the functional groups of the active components. SEM images brought out that the particles were spherical in shape, and the size was found to be ranging under 70 rim. Further, the synthesized CuO NPs were tested for antibacterial activity by standart disc diffusion method. The nanoparticles were found to have antibacterial activity against pathogenic bacterial strains Escherichia coli and Staphylococcus aureus by the observation of inhibition zones around each well.
Keywords: Copper nanoparticles; green method; antibacterial activity; Ocimum basilicum leaf extract; ONE-STEP SYNTHESIS; SILVER NANOPARTICLES; LEAF EXTRACT; BIOLOGICAL SYNTHESIS; NANO PARTICLES; METAL-IONS; INACTIVATION; ADSORPTION; COLI; Environmental Sciences & Ecology